2013
DOI: 10.1002/ep.11790
|View full text |Cite
|
Sign up to set email alerts
|

Potential of locally available products for use as binders in producing fecal compost pellets in ghana

Abstract: Market studies in Ghana have revealed a potential for composted or cocomposted fecal matter as nutrient source inputs for agricultural production. To increase the marketability of such products, high nutrient value and easier handling/transporting options are among the significant factors which drive demand. Pelletization is seen as a potentially interesting option to address these challenges. To preserve form stability of the pellet products, the addition of a binding material during the pelletization process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…
Fortifer™ is a soil amendment certified by the Ministry of Food and Agriculture of Ghana. It is a matured compost produced from dewatered faecal sludge (DFS) and sawdust or market waste, and the nitrogen content enriched up to 3.0% (Adamtey et al, 2009) using composting and pelletization processes (Nikiema et al, 2014). Being an organo‐mineral (mixture of organic and inorganic fertilizer), Fortifer™ is rich in organic matter as well as micronutrients such as zinc, iron, copper and manganese (Adamtey et al, 2009).
…”
Section: Methodsmentioning
confidence: 99%
“…
Fortifer™ is a soil amendment certified by the Ministry of Food and Agriculture of Ghana. It is a matured compost produced from dewatered faecal sludge (DFS) and sawdust or market waste, and the nitrogen content enriched up to 3.0% (Adamtey et al, 2009) using composting and pelletization processes (Nikiema et al, 2014). Being an organo‐mineral (mixture of organic and inorganic fertilizer), Fortifer™ is rich in organic matter as well as micronutrients such as zinc, iron, copper and manganese (Adamtey et al, 2009).
…”
Section: Methodsmentioning
confidence: 99%
“…FS that has undergone some degree of treatment and is no longer raw is called -treated sludge‖. Treated sludge, which is fully stabilised sludge, can be used for different purposes such as combustion as fuel (Werther & Ogada, 1999;Muspratt et al, 2014;Strande et al, 2014), char production (Rulkens, 2008), in building materials (Jordan et al, 2005;Lin et al, 2012) and as a soil conditioner (Nikiema et al, 2013;Diener et al, 2014). Use of treated or raw sludge as a soil conditioner and fertiliser is very popular.…”
Section: Benefits Of Treated Sludgementioning
confidence: 99%
“…Farmers of Dakar use, on average, 246 m 3 of FS per year as a soil conditioner. In Ghana, co-composting from FS has previously shown limited demand by farmers, but nitrogen enrichment is suggested to increase value and demand (Nikiema et al, 2013). The average price is US$4/tonne for FS that is generated from drying beds, in contrast to animal manure, which sells at twice as much due to its higher acceptance (Diener et al, 2014).…”
Section: Benefits Of Treated Sludgementioning
confidence: 99%
“…Criteria to be considered for selection of a binder include binding ability/strength (to avoid the use of high amounts of binder), availability of binder, its handling and storage requirements, ease of use during pelletization and cost as well as its impact on pellets; for example disaggregation rate, nutrient content, etc. (Nikiema Preliminary investigations revealed that cassava starch and clay were possible binding materials that can be used for pelletization in Ghana given their availability (Nikiema et al 2014). Comparing the performance of these two materials, i.e.…”
Section: Advantagesmentioning
confidence: 99%